2002
DOI: 10.1073/pnas.182384499
|View full text |Cite
|
Sign up to set email alerts
|

1-Cys peroxiredoxin overexpression protects cells against phospholipid peroxidation-mediated membrane damage

Abstract: 1-Cys peroxiredoxin (1-cysPrx) is a novel antioxidant enzyme able to reduce phospholipid hydroperoxides in vitro by using glutathione as a reductant. This enzyme is widely expressed and is enriched in lungs. A fusion protein of green fluorescent protein with 1-cysPrx was stably expressed in a lung-derived cell line (NCI-H441) lacking endogenous enzyme. Overexpressing cells (C17 or C48) degraded H 2O2 and t-butylhydroperoxide more rapidly and showed decreased sensitivity to oxidant stress as measured by 51

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
170
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(181 citation statements)
references
References 27 publications
11
170
0
Order By: Relevance
“…Previous studies have demonstrated that overexpression of 1-cysPrx in NIH 3T3 cells enhances their ability to reduce H 2 O 2 and protects their glutamine synthetase against H 2 O 2 -mediated inactivation (12). Our laboratory has shown that 1-cysPrx can reduce peroxidized membrane phospholipids in H441 cells, a lung epithelial cell line (17), whereas an antisense-mediated decrease in expression of 1-cysPrx in L2 cells, another lung epithelial cell line, resulted in apoptotic cell death (20). Recently, gene-targeted mice with absent 1-cysPrx have been shown to be more sensitive to paraquat-induced oxidative injury (23).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Previous studies have demonstrated that overexpression of 1-cysPrx in NIH 3T3 cells enhances their ability to reduce H 2 O 2 and protects their glutamine synthetase against H 2 O 2 -mediated inactivation (12). Our laboratory has shown that 1-cysPrx can reduce peroxidized membrane phospholipids in H441 cells, a lung epithelial cell line (17), whereas an antisense-mediated decrease in expression of 1-cysPrx in L2 cells, another lung epithelial cell line, resulted in apoptotic cell death (20). Recently, gene-targeted mice with absent 1-cysPrx have been shown to be more sensitive to paraquat-induced oxidative injury (23).…”
mentioning
confidence: 80%
“…Protein samples (10 g) were subjected to a 12% SDS-PAGE gel on a XCell electrophoresis apparatus (Invitrogen, Carlsbad, CA) and then were transferred to a polyvinylidene fluoride membrane (Millipore, Bedford, MA). Membranes were incubated in blocking solution (0.1% Tween 20-TBS buffer containing 10% nonfat dry milk; Bio-Rad, Richmond, CA) for 1 h and then were probed with a polyclonal antibody (1:2,000 dilution) to a 1-cysPrx peptide (1: 2,000 dilution) followed by peroxidase-conjugated secondary antibody as described previously (17,20). The reaction was detected by enhanced chemiluminescence (ECL; NEN Life Science, Bos- ton, MA) and quantitated by densitometric scanning of X-ray film using the FluorS multi-imager (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of them have two conserved and catalytically active Cys residues (PRDX1 to 5), though only that of the N-terminal region is directly involved in peroxidatic activity. PRDX6 only has the catalytic Cys residue of the N-terminal region and thus belongs to 1-Cys PRDX subclass with both glutathione peroxidase and phospholipase A activities leading to reduced membrane phospholipid peroxidation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…1-cys Prx is one of six Prx isoforms, and is expressed in various tissues -in particular liver tisses -related to the protection of cellular oxidative stresses (10).…”
Section: Introductionmentioning
confidence: 99%